2014
DOI: 10.7745/kjssf.2014.47.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of co-inoculation of Brevibacterium iodinum RS16 and Methylobacterium oryzae CBMB20 on the early growth of crop plants in Saemangeum reclaimed soil

Abstract: The objective of this study was to determine the effect of single and co-inoculation of plant growth promoting bacteria (PGPB) on early plant growth in Saemangeum reclaimed soil. Plant growth promoting Brevibacterium iodinum RS16 and Methylobacterium oryzae CBMB20 were inoculated on maize (Zea mays L.) and sorghum-sudangrass hybrid (Sorghum bicolor L.) grown in Saemangeum reclaimed soil. Single and co-inoculation of B. iodinum RS16 and M. oryzae CBMB20 increased plant height, dry biomass accumulation and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Meanwhile, previously, co-inoculation of PGPB during the early developmental stage on plants grown in Saemangeum reclaimed soil showed that plant growth-promoting B. iodinum RS16 and M. oryzae CBMB20 increased plant height, dry biomass accumulation and macro-nutrient accumulation of maize and a sorghum-sudangrass hybrid. Macronutrient accumulation (P, K, Ca and Mg) was higher with M. oryzae CBMB20 treatment compared to the non-inoculated treatment, while B. iodinum RS16 treatment increased N, Ca and Mg accumulation compared to the non-inoculated treatment (Kim et al, 2014). Another report found that inoculation with Actinomycetes NB 1 , AVermi7, YB6y and NB 3 in combination with a full rate of fertilization significantly increased P uptake by 80 to 136% over the non-inoculated control (Cruz et al, 2014).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Meanwhile, previously, co-inoculation of PGPB during the early developmental stage on plants grown in Saemangeum reclaimed soil showed that plant growth-promoting B. iodinum RS16 and M. oryzae CBMB20 increased plant height, dry biomass accumulation and macro-nutrient accumulation of maize and a sorghum-sudangrass hybrid. Macronutrient accumulation (P, K, Ca and Mg) was higher with M. oryzae CBMB20 treatment compared to the non-inoculated treatment, while B. iodinum RS16 treatment increased N, Ca and Mg accumulation compared to the non-inoculated treatment (Kim et al, 2014). Another report found that inoculation with Actinomycetes NB 1 , AVermi7, YB6y and NB 3 in combination with a full rate of fertilization significantly increased P uptake by 80 to 136% over the non-inoculated control (Cruz et al, 2014).…”
Section: Discussionmentioning
confidence: 86%
“…Only 17% of these lands have a salinity level that is acceptable for crop cultivation and the remaining 83% of the land has been deemed unsuitable for crop growth due to high salt levels. This land also has several other drawbacks such as limited macroand micronutrients, restricted organic matter and physical and chemical properties that do not promote a good crop yield (Kim et al, 2014). Thus, these areas will require an integrated management strategy.…”
Section: Discussionmentioning
confidence: 99%